IDENTIFIKASI TINDAKAN PENGAWASAN DAN PENCEGAHAN TERHADAP KEJAHATAN FINANSIAL PERBANKAN SYARIAH SELAMA MASA PANDEMI COVID 19 - Asyari Hasan; Lulu Febriany (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The increasingly widespread banking crimes during the 19th council, resulted inthe need for strengthening all efforts to prevent and eradicate these bankingcrimes. Supervision also becomes one of the alternatives. Supervision of the bankwas also seen as very important during the covid pandemic 19 period in order tomaintain public confidence (customers) in the bank itself and to be able toachieve and maintain the stability of the rupiah, as the objective of BankIndonesia. The forms of supervision are external supervision, internalsupervision and public supervision and comply with compliance aspects ofIslamic banking. If it runs effectively, it is certain that banking crime can beminimized and no longer colors the banking industry